Saturation flow versus green time at two‐stage signal controlled intersections - Boumediene, Ahmed; Brahimi, Kouider; Belguesmia, Noreddine; Bouakkaz, Khaled (Transport, 2009)
Intersections are the key components of road networks considerably affecting capacity. As flow levels and experience have increased over the years, methods and means have been developed to cope with growing demand for traffic at road junctions. Among various traffic control devices and techniques developed to cope with conflicting movements, traffic signals create artificial gaps to accommodate the impeded traffic streams. The majority of parameters that govern signalised intersection control and operations such as a degree of saturation, delays, queue lengths, the level of service etc. are very sensitive to saturation flow. Therefore, it is essential to reliably evaluate saturation flow for correctly setting traffic signals to avoid unnecessary delays and conflicts. Generally, almost all guidelines support the constancy of saturation flow irrespective of green time duration. This paper presents the results of field studies carried out to enable the performance of signalised intersections to be compared at different green time durations. It was found that saturation flow decreased slightly with growing green time. Reduction corresponded to between 2 and 5 pcus/gh per second of green time. However, the analyses of the discharge rate during the successive time intervals of 6‐seconds showed a substantial reduction of 10% to 13% in saturation flow levels after 36 seconds of green time compared to those relating to 6–36 seconds range. No reduction in saturation flow levels was detected at the sites where only green periods of 44 seconds or less were implemented. First published online: 27 Oct 2010